Endocytosis of Wnt ligands from surrounding epithelial cells positions microtubule nucleation sites at dendrite branch points. - Thyagarajan, P.; Mirshahi, H.S.; Kothe, G.O.; Kumar, N.; Long, M.; Abimbola, B.S.; Weiner, A.T.; Rolls, M.M. (PLoS Biology, 2025)
Microtubule nucleation is important for microtubule organization in dendrites and for neuronal injury responses. The core nucleation protein, ?Tubulin (?Tub), is localized to dendrite branch points in Drosophila sensory neurons by Wnt receptors and scaffolding proteins on endosomes. However, whether Wnt ligands are important is unknown. We found that Wnt secretion from epithelial cells was required for ?Tub localization to dendrite branch points. Using RNAi and mutant approaches, we demonstrated that Wnt4 and wntD both position ?Tub. Moreover, injury-induced increases in neuronal microtubule dynamics required Wnt secretion from epithelial cells. Overexpression of Wnts in epithelial cells increased microtubule dynamics to the same extent as axon injury indicating surrounding cells have an instructive role in neuronal nucleation. To determine how Wnt ligands concentrate microtubule nucleation at dendrite branch points, we tested whether endocytosis is restricted to specific regions of dendrites. Markers of clathrin-mediated endocytosis localized to puncta at branch points. Behavior of these puncta was sensitive to inhibition of endocytosis suggesting they represented endocytic sites. In addition to previously described colocalization of Wnt receptors and scaffolds with Rab5 endosomes, we identified a separate set of Wnt signaling puncta that colocalized with clathrin in dendrites. Moreover, ?Tub and Wnt scaffolding protein recruitment to branch points was reduced by clathrin RNAi, and injury-induced up-regulation of microtubule dynamics was sensitive to clathrin reduction. We propose that the localization of Wnt endocytic sites to dendrite branch points results in the local generation of microtubule nucleating endosomes.